Association of shift work with mood disorders and sleep problems according to chronotype: a 17-year cohort study. (3rd April 2021) - Cheng, Wan-Ju; Puttonen, Sampsa; Vanttola, Päivi; Koskinen, Aki; Kivimäki, Mika; Härmä, Mikko
ABSTRACT: Both evening chronotype and shift work are associated with depressive symptoms. This study examined whether the association between shift work and mood disorders and sleep problems varies by chronotype. The study population included 10637 participants from the Finnish Hospital Personnel Cohort Study. Work schedule was assessed using repeated questionnaires between 2000 and 2017. Chronotype, assessed using a single item from the Diurnal Type Scale, was categorized into definite morning, somewhat morning, somewhat evening, and definite evening types. The presence of mood disorders was identified by the 12-item General Health Questionnaire. Sleep problems were assessed by self-reported frequency of difficulty falling asleep and maintaining asleep. Longitudinal fixed effects models were used to examine the associations between shift work and the presence of mood disorders and sleep problems, stratified by chronotype. We found that fixed night work was associated with mood disorders among somewhat evening (adjusted odds ratio [OR] 1.91, 95% CI 1.09–3.34) and definite evening-type workers (adjusted OR 2.05, 95% CI 1.06–3.98). Shift work with night shifts was associated with mood disorders among definite evening-type workers (adjusted OR 1.75, 95% CI 1.18–2.60). Similarly, fixed night work was associated with difficulty maintaining sleep only among evening-type workers. In conclusion, evening chronotype increase the vulnerability to mood disorders and sleep disturbances related to night work.